2011
DOI: 10.1017/s1368980011002072
|View full text |Cite
|
Sign up to set email alerts
|

Revision of food-based dietary guidelines for Ireland, Phase 1: evaluation of Ireland's food guide

Abstract: Objective: To evaluate Ireland's food-based dietary guidelines and highlight priorities for revision. Design: Evaluation with stakeholder input. Energy and nutrient intake goals most appropriate for Ireland were determined. Advice from Ireland's food guide was translated into 4 d food intake patterns representing age and gender groups from 5 to 511 years. Nutritional content of the food patterns was compared with identified goals and appropriateness of food advice was noted. Feedback from stakeholders was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…In essence, there is a lack of comprehensive data on consumer understanding of SS guidance (19) . In general, consumer estimations of PS, particularly of breakfast cereals (8) , tend to deviate from the suggested or recommended SS (5,(20)(21)(22)(23) . The 5-a-day message is widely recognised guidance for fruit and vegetables (24) yet consumers have expressed their uncertainty as to what equates to a SS (9) .…”
mentioning
confidence: 99%
“…In essence, there is a lack of comprehensive data on consumer understanding of SS guidance (19) . In general, consumer estimations of PS, particularly of breakfast cereals (8) , tend to deviate from the suggested or recommended SS (5,(20)(21)(22)(23) . The 5-a-day message is widely recognised guidance for fruit and vegetables (24) yet consumers have expressed their uncertainty as to what equates to a SS (9) .…”
mentioning
confidence: 99%
“…Functional vitamin D deficiency is an even more prominent concern, with a number of studies reporting inadequate intakes among the Irish population [64,65], and 76 % of Irish adults now demonstrating low serum levels of this vitamin on a year round basis [66]. Indeed, so endemic is this insufficiency that the Food Safety Authority of Ireland in their 2011 revision of Ireland's healthy eating guidelines, recommended that all people in Ireland should take a vitamin D supplement [67].…”
Section: The Irish Situationmentioning
confidence: 99%
“…There is also well-established evidence that the prevalence of obesity is higher among those from socio-economically disadvantaged groups (13,14) . To provide optimal nutrition in the context of obesity prevention, Ireland's national food guide (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) was recently evaluated in order to identify and prioritize the areas most in need of revision (15) . This evaluation found that food patterns based on the current food guide provided excessive energy, total and saturated fat but inadequate fibre and vitamin D intakes (15) .…”
mentioning
confidence: 99%
“…Surveys in Ireland have indicated that access to affordable, good-quality, nutritious foods is a major challenge to low-income families and that social disadvantage is associated with higher fat intakes (19,20) . Following the evaluation of Ireland's food guide (1993-2010) (15) , the present paper describes the approaches used for revision of dietary guidelines in Ireland and the recommendations for healthy eating advice that were formulated as a result. In addition, the paper includes an examination of the affordability of these new recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation